2016
DOI: 10.1080/14697688.2016.1183035
|View full text |Cite
|
Sign up to set email alerts
|

Risk premia: asymmetric tail risks and excess returns

Abstract: We present extensive evidence that "risk premium" is strongly correlated with tail-risk skewness but very little with volatility. We introduce a new, intuitive definition of skewness and elicit an approximately linear relation between the Sharpe ratio of various risk premium strategies (Equity, Fama-French, FX Carry, Short Vol, Bonds, Credit) and their negative skewness. We find a clear exception to this rule: trend following has both positive skewness and positive excess returns. This is also true, albeit les… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(41 citation statements)
references
References 36 publications
2
39
0
Order By: Relevance
“…• First, as is now well known, volatility in itself does not entail risk premia, as the Low-Vol anomaly illustrates Ang et al (2009) • Second, the skewness of SMB portfolios is only weakly negative, and those of CMH virtually unskewed, at odds with what one should expect for risk premium strategies (see the extended discussion in Lempérière et al (2017)). …”
Section: Correcting Biases: the Cmh Portfoliomentioning
confidence: 56%
“…• First, as is now well known, volatility in itself does not entail risk premia, as the Low-Vol anomaly illustrates Ang et al (2009) • Second, the skewness of SMB portfolios is only weakly negative, and those of CMH virtually unskewed, at odds with what one should expect for risk premium strategies (see the extended discussion in Lempérière et al (2017)). …”
Section: Correcting Biases: the Cmh Portfoliomentioning
confidence: 56%
“…In other words, the performance appears to become worse than average in periods of high market volatility: at least in aggregate, hedge funds have difficulty fulfilling their promises in terms of tail diversification (see [3] for a detailed analysis of hedge fund performance). A related observation was made in [4], where it was shown that the performance of the HFRI Index has a significant skewness, making its performance akin to that of shorting volatility.…”
Section: Introductionmentioning
confidence: 87%
“…The skewness of the profit and loss distribution of a given strategy was recently proposed as a natural discriminant between risk premia strategies and genuine market anomalies (see [4] for a thorough discussion). Several previous papers have pointed out that the skewness of trend following is positive (see [16,17], and [18] for a general framework), at variance with risk premia that have a negative skewness.…”
Section: Skewness Of Trend Following Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, while well-known risk premia strategies are indeed rewarding investors for carrying a significant negative skewness risk (see e.g. Harvey and Siddique (2000), Lemperiere et al (2014)), quality strategies are in fact found to have a positive skewness and a very small propensity to crash -see (1) ( This table describes the risk-return profile of 8 well-known quantitative long-short strategies and long the market itself, using monthly returns. See Appendix for details on data, signal, and portfolio construction.…”
Section: Risk Premium or Behavioral Anomaly?mentioning
confidence: 99%